The perceptive image of volunteering and its relationship to the motives towards volunteering among a sample of Al-Quds Open University students. (Journal Of Educational and Psychological Researches, 2022)
This study aimed to identify the perceived mental image of volunteering, and its relationship to volunteer motivation among a sample of Al-Quds Open University students, as well as to identify the differences in the perceived mental image of volunteering due to variables (gender, year of study, place of residence, college). The researcher has used relational descriptive approach. The researcher has used two questionnaires, the first was used to measure the perceptive mental image of volunteering, and the second to measure the motivation towards volunteering, and the study population may consist of all students of Al-Quds Open University Hebron Branch during the first semester of the academic year 2021/2020 and their number (3462)Male and female students. The study sample consisted of (246) male and female students who were chosen using the stratified sample method. The results showed that there were no statistically significant differences in the perceptive mental image of volunteering due to the variables (gender, school year, place of residence, college) while it showed a positive relationship between the perceptive mental image of volunteerism and the motivation towards volunteer work. Accordingly.(170 words)